2019
DOI: 10.20431/2454-6380.0504001
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with an Antioxidant Rich Oil Does Not Influence Blood Lactate, Rate of Perceived Exertion and Muscle Soreness after Resistance Exercise

Abstract: Pequi (Caryocar brasiliense) is a fruit from Brazil with antioxidant properties. Previous research suggested that it could be a candidate for sports ergogenic aid. However, little is known about pequi supplementation and sports performance. Aim: to analyze the effect of pequi oil supplementation on blood lactate, rate of perceived exertion and muscle soreness after a resistance exercise session. Twelve men (21.1±2.6 years, 77.0±10.5 kg, 24.3±1.9 Kg/m²) underwent pequi supplementation for 14 days. Before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…However, the present investigation did not corroborate those studies, as no effect of the supplementation was observed in any of the dependent variables both within and between groups. Interestingly, this is consistent with previous studies that analyzed young, healthy, and physically active people after 14 and 30 days of supplementation combined with resistance exercise and did not show any effect of the supplementation in acute and chronic SBP, DBP, HR, DP, as well as total cholesterol, triglycerides, and acute blood lactate, rate of perceived exertion and 24-hour muscle soreness (CLAEL et al, 2020;DUTRA et al, 2019;LEITE et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…However, the present investigation did not corroborate those studies, as no effect of the supplementation was observed in any of the dependent variables both within and between groups. Interestingly, this is consistent with previous studies that analyzed young, healthy, and physically active people after 14 and 30 days of supplementation combined with resistance exercise and did not show any effect of the supplementation in acute and chronic SBP, DBP, HR, DP, as well as total cholesterol, triglycerides, and acute blood lactate, rate of perceived exertion and 24-hour muscle soreness (CLAEL et al, 2020;DUTRA et al, 2019;LEITE et al, 2020).…”
Section: Discussionsupporting
confidence: 91%